2019
DOI: 10.21608/adjalexu.2019.57612
|View full text |Cite
|
Sign up to set email alerts
|

Veneering Thickness Effect on the Optical Properties of Peek Restorations (In Vitro Study)

Abstract: INTRODUCTION: Polyetheretherketone (PEEK) can be used as a core material for fixed prosthodontics. However, information about the optimum veneer thickness of veneered PEEK restorations is still scarce. OBJECTIVES: To evaluate the effect of different composite veneer thickness on the optical properties of PEEK restorations. MATERIALS AND METHODS: Twenty four (n=24) PEEK (BioHPP granules) core disc-shape specimens of 15 mm diameter and 0.8 mm thickness were fabricated and veneered with composite resin (crea-lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Color matching in composite resin restorations is not an easy task, especially in cases of severe tooth discoloration and in through and through restorations, as in these situations there is not enough or normal adjacent tooth structure and usually a grayish appearance will be seen in the final composite restoration, which fails color matching [ 5 ]. Complete masking of tooth discoloration through direct restorations is a complex procedure due to the translucency of the composite resins [ 6 8 ] and requires careful diagnosis, treatment planning, and the use of the correct restorative technique to reach the acceptable outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Color matching in composite resin restorations is not an easy task, especially in cases of severe tooth discoloration and in through and through restorations, as in these situations there is not enough or normal adjacent tooth structure and usually a grayish appearance will be seen in the final composite restoration, which fails color matching [ 5 ]. Complete masking of tooth discoloration through direct restorations is a complex procedure due to the translucency of the composite resins [ 6 8 ] and requires careful diagnosis, treatment planning, and the use of the correct restorative technique to reach the acceptable outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, samples veneered with 0.5 mm resin composite had statistically higher values than 1mm thick samples. Such a result was supported by the El-Sawaf et al [22] study that showed that increasing the thickness of composite veneer will reduce the ΔE values significantly. It was then concluded that a 0.5 mm thickness of a composite veneer layer is considered unacceptable because it allows for a significant increase in light transmission with a significant decrease of masking ability.…”
Section: Discussionmentioning
confidence: 73%
“…If the ΔE is greater than 1 and less than 3.3, it's considered to be detectable by a skilled operator, but clinically accepted. But if the ΔE is greater than 3.3, it's regarded to be unacceptable because it could be detected by untrained observers [22].…”
Section: Palavras-chavementioning
confidence: 99%